Jurisprudence’s itineraries regarding the imposed exclaustration - Michowicz, Przemysław (Prawo Kanoniczne, 2023)
This essay has basically two objectives: firstly, to demonstrate the coherence and non-contradictory nature of the jurisprudence in question and, secondly, to establish the existence of prevalent jurisprudence to which any form of jurisprudential chaos is extraneous. To achieve these goals, the jurisprudence of the Supreme Tribunal of the Apostolic Signatura will be analyzed, preceded by this analysis with historical references to the legal institution of the imposed exclaustration, also called ad nutum Sactæ Sedis. What is relevant therefore is the merely practical aspect of this work since the legal institution of the imposed exclaustration is already well studied and carefully commented on by the doctrine.